EFEKTIVITAS PROGRAM SI BENING DALAM RANGKA PENURUNAN STUNTING DI KECAMATAN SEMARANG UTARA - Duta Al Aisy Baraldi Yusuf; Rina Martini (Journal of Politic and Government Studies, 2026)
Stunting is a chronic nutritional problem that hinders children's physical and cognitive development. Semarang Utara District recorded the highest stunting prevalence in Semarang City, necessitating an evaluation of the effectiveness of the Semua Ikut Bergerak Bersama Menangani Stunting (Si Bening) Program in this area. This study aims to analyze the effectiveness of the Si Bening Program in reducing stunting and to identify the inhibiting factors in Semarang Utara District.This study employed a descriptive qualitative method, with data collection techniques including in-depth interviews, observation, and documentation. The effectiveness analysis was based on Duncan and Steers' theory, which encompasses three dimensions: goal achievement, integration, and adaptation. The results of the study indicate that the implementation of the Si Bening Program in Semarang Utara District has not been fully effective. In the goal achievement dimension, although nutritional interventions have been conducted, stunting rates remain fluctuant due to the emergence of new cases that are not proportional to the recovery rates. In the integration dimension, cross-sector coordination between the government and health workers has functioned very well; however, community participation in nutritional education activities remains low and inconsistent. Meanwhile, in the adaptation dimension, the program faced challenges in adjusting strategies to the characteristics of coastal areas and limited funding at the sub-district level. The conclusion of this study shows that program effectiveness is hindered by economic factors, inconsistent family parenting patterns, and a heavy reliance on community self-help funds. To improve effectiveness, it is recommended to strengthen budget regulations at the sub-district level and transform digital-based communication strategies to encourage active participation and independent community awareness in fulfilling children's nutrition.